Stimuli‐responsive magnesium‐based materials for biomedical applications: A review - Xianli Wang; Yanbin Zhao; Qiangsheng Dong; Chenglin Chu; Feng Xue; Cheng Wang; Jing Bai (Responsive Materials)
Abstract As one of the revolutionizing biodegradable metals, Magnesium (Mg) has gained global attention from researchers due to positive clinical feedback in bone fixation and cardiovascular repair. In many cases, researchers attributed its biological effects to the degradation products of Mg, overlooking the interactions between Mg and the microenvironment within bodies, as well as the additional effects of physical/chemical reactions induced by endogenous and exogenous stimuli on tissues. In recent years, the academic community has increasingly focused on the stimuli responsiveness of Mg‐based materials for tissue repair and disease treatment. However, there is a lack of systematic summaries on the “composition‐structure‐function” relationships when Mg‐based materials are applied in various physiological scenarios. To address this gap, this review summarizes the biological effects of Mg‐based materials under endogenous and exogenous stimuli over the past decade. Endogenous stimuli mainly include changes in spontaneously released Mg2⁺ ions concentration, pH variations, body fluid infiltration, reactive oxygen species intervention, temperature changes, and enzyme involvement. Exogenous stimuli primarily involve external fields such as photo‐irradiation, electric field, magnetic field, ultrasound, and mechanical stress. By activating these endogenous/exogenous stimuli, the specific functions of Mg‐based materials can be triggered as needed, leading to more pronounced therapeutic effects compared to the non‐stimulated state. Accordingly, we also analyze the mechanisms underlying the enhanced biological impact. Based on existing research, this review further examines the limitations of studies under different stimulation scenarios and proposes suggestions for future research improvements. Ultimately, we hope this review could provide new insights for the efficient clinical application of Mg‐based materials in the future.